2019
DOI: 10.1002/chem.201901534
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of N‐Heterocyclic Carbene‐Stabilized Copper Nanoparticles from an N‐Heterocyclic Carbene–Borane

Abstract: N‐Heterocyclic carbene (NHC)‐stabilized copper nanoparticles (NPs) were synthesized from an NHC–borane adduct and mesitylcopper(I) under thermal conditions (refluxing toluene for 2.5 h). NPs with a size distribution of 11.6±1.8 nm were obtained. The interaction between Cu NPs and NHC ligands was probed by X‐ray photoelectron spectroscopy, which showed covalent binding of the NHC to the surface of the NPs. Mechanistic studies suggested that NHC–borane plays two roles: contributing to the reduction of [CuMes]2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 47 publications
(86 reference statements)
2
23
0
Order By: Relevance
“…24,26−28 Indeed, covalent interactions have been proposed to characterize NHC-to-gold nanoparticle (AuNP) binding. NHC molecules have been explored as stabilizing agents for transition metal-rich NPs (e.g., those with cores made of Au, 29−32 Ru, 33,34 Pd, 35,36 Co, 37 and Ir 38 ) and upconverting NPs. 39 In addition, using well-thought synthetic rationales, NHCs can be easily modified by attaching diverse functional groups to finely tune their steric and electronic properties.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,26−28 Indeed, covalent interactions have been proposed to characterize NHC-to-gold nanoparticle (AuNP) binding. NHC molecules have been explored as stabilizing agents for transition metal-rich NPs (e.g., those with cores made of Au, 29−32 Ru, 33,34 Pd, 35,36 Co, 37 and Ir 38 ) and upconverting NPs. 39 In addition, using well-thought synthetic rationales, NHCs can be easily modified by attaching diverse functional groups to finely tune their steric and electronic properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Given its ability to share two electrons, NHC is considered a soft Lewis base, which implies that moieties presenting this group exhibit strong affinity to gold and other transition metal nanocrystal surfaces because of the soft Lewis acidic character of these materials. , Indeed, covalent interactions have been proposed to characterize NHC-to-gold nanoparticle (AuNP) binding. NHC molecules have been explored as stabilizing agents for transition metal-rich NPs (e.g., those with cores made of Au, Ru, , Pd, , Co, and Ir) and upconverting NPs . In addition, using well-thought synthetic rationales, NHCs can be easily modified by attaching diverse functional groups to finely tune their steric and electronic properties. , These findings have made them very appealing for many research areas, including organometallic chemistry and catalysis. ,, Previous studies have shown that NHC-functionalized AuNPs with either bidentate NHC or NHC attached to a hydrophilic poly­(ethylene glycol), PEG, moiety can provide stability to the nanocrystals over a broad range of pH buffers for a few weeks. …”
Section: Introductionmentioning
confidence: 99%
“…Both the NHC-boryl radical and amidyl radical can be successfully trapped by TEMPO (See Supporting Information for details). [15] In addition, in our radical hydroboration process, a full b-regioselectivity was obtained (Scheme 5 a). However, for the same substrate [Scheme 5, Eq.…”
Section: Angewandte Chemiementioning
confidence: 86%
“…The 2,2,6,6‐tetramethyl‐1‐piperidyloxy (TEMPO) and 1,4‐dinitrobenzene can completely inhibit the hydroboration, suggesting that a radical process may be likely. Both the NHC‐boryl radical and amidyl radical can be successfully trapped by TEMPO (See Supporting Information for details) . In addition, in our radical hydroboration process, a full β‐regioselectivity was obtained (Scheme a).…”
Section: Methodsmentioning
confidence: 91%